Conocimiento de evaluación formativa en la elaboración de instrumentos de evaluación en estudiantes de Educación Inicial de práctica pre profesional Facultad de Ciencias de la Educación y Humanidades Iquitos 2022 - Cisneros Montes, Jenny Jackeline (2025)
The fundamental purpose of this study was to explain the influence of knowledge about formative assessment on the development of assessment tools among early childhood education students in pre-professional practice at the Faculty of Education and Humanities, Iquitos, 2022. To achieve this, a bivariate, field-based, longitudinal research design with an explanatory type was employed. Data collection was conducted through the survey technique, using a questionnaire and a written knowledge test as instruments, both of which were previously validated. The population and sample consisted of 33 students. The results obtained showed that the Regulatory (DR), Procedural (DP), Continuous (DC), and Feedback (DRET) dimensions had a significant and positive influence on knowledge of formative assessment. This finding was supported by a high correlation (R=0.923) and a coefficient of determination (R²=0.851), indicating that these dimensions explained 85.1% of the variability in formative assessment, highlighting their relevance to improving evaluative processes.